Reasons Behind The Concentration of Two-Stroke Three Wheelers and The Impacts on Urban Khulna City, bangladesh - Kazi Saiful Islam; khan Rubayet (Journal of Regional and City Planning, 2003)
Two-stroke three wheelers are playing a big role in transporting people especially the commuters in Khulna City. These so-called baby-taxies are very popular mode of transportation in most of big cities in Bangladesh because of low maintenance costs and low travel costs. However, these vehicles caused severe air pollution and congestion in the city. As a result Dhaka (the capital of Bangladesh) banned these vehicles for operating In its area from January 1, 2003 to allow clean air and avoid traffic congestion to some extent. Afterwards, many people lost their jobs and the vehicles remained useless for the capital city. The baby-taxi owners from other cities of Bangladesh showed their interests to bring them in their own areas with a minimum cost so that they can explore some new routes and can offer some new jobs as well. This study attempted to explore the reasons of concentrating these vehicles in Khulna City and the new impacts in the city area in regards to city environment. Primary data base has been used here to show the numbers of vehicles and to show the newly explored routes in map. Finally the paper concludes with some problems that can be further studied for minimizing the possible upcoming threats in the city's environment.